Examining the influence of high commitment human resources practices (HRM) on academics' organizational commitment and mediating effects of career commitment and perceived or organizational support, trust, and procedural justice - Lew, Tek (Taiwan Institute of Business Administration, 2008)
Much recent writing on Human Resource Management (HRM) has emphasized the desirability of a committed workforce and the central role of HRM practices in establishing and maintaining employee commitment. However, little research has examined the psychological links of career commitment, perceived organizational support, /trust/and procedural justice according to the social exchange theory which underlines the relationship of HRM practices on employee commitment, especially in the context of higher education in Malaysia. Hence, this review and conceptual paper makes a timely contribution to the research literature by reviewing the relevant literature and recommending propositions to guide future research in this area for faculty members at higher educational institutions in Sarawak, Malaysia. Theoretically, it adopts the social exchange theory by incorporating the mediating effects of career commitment, perceived organizational support, /trust/and procedural justice into the above relationship between high commitment human resource management practices (HRM) and employee commitment.